Cases in online interview research - Salmons, Janet , 1952- (SAGE, 2012)
In an era of constrained research budgets, online interviewing opens up immense possibilities: A researcher can literally conduct a global study without ever leaving home. But more than a decade after these technologies started to become available, there are still few studies on how to utilize online interviews in research. This book provides 10 cases of research conducted using online interviews, with data collected through text-based, videoconferencing, multichannel meeting, and immersive 3-D environments. Each case is followed by...